Gall Rust Disease Of 'Batai' [Falcataria Moluccana (Miq.) Barneby & J.W. Grimes]In Sabah, Malaysia - Sri, Sri Rahayu (2007)

(untitled)
Batai (Falcataria moluccana (Miq.) Barneby and J.W. Grimes) is one of the valuable multipurpose tree species for forest plantations in Malaysia and Indonesia. However, since 1993, gall rust disease has been identified as a dangerous malady of batai causing severe damage to all growth stages of the plant from seedlings in the nursery to mature trees in the field. Thus, the objectives of this study were to evaluate the environmental factors affecting disease development, to characterize and identify the gall rust fungus and gall rust symptoms, to screen F. moluccana seedlings from eleven seed sources for growth and gall rust disease resistance, and to assess the genetic variation of those seed sources and its relationship with gall rust disease severity.Based on the result from the step-wise multiple regression analysis, it was found that open sites with flat topography, preferably without the occurrence of fog did not favour gall rust disease development. In addition, silvicultural treatments such as pruning, thinning and clear cutting were able to reduce gall rust disease incidence and severity. Relative humidity and wind speed were two meteorological factors which were significantly associated with the incidence and severity of gall rust disease. High relative humidity (RH ≥ 90%) and slow wind speed (WS ≤ 80 km/hours), was found to promote gall rust disease development. In addition, it appeared that the spread of gall rust spores originated from the north, probably from the Philippines to Brumas Estate, Tawau, Sabah, Malaysia. Gall rust disease on F. moluccana in Brumas Estate, is caused by the gall rust fungus Uromycladium tepperianum (Sacc.) McAlp., family: Pileolariaceae, order: Uredinales class: Urediniomycetes. The fungus produces teliospores which have ridged longitudinal striations, with three spores on each head. The size of the teliospores ranged from 13-18 μm wide and 17-26 μm long. The fungus completed entire life cycle on one host, i.e. F. moluccana. This study confirmed that the teliospores cannot themselves infect the host; they have to germinate to produce basidiospores, which are formed at least 10 hours after inoculation. Then a penetration peg was formed by a matured basidiospore 16 hours after inoculation, penetrates the host cells directly through the epidermis. Seven days after inoculation (DAI), vegetative mycelia of this gall-forming rust give rise to pycnia, recognized as small brown pustule which breaks through the epidermis. The typical symptom of gall rust disease on the seedlings is bending of the stem or shoot, either with or without the formation of a dark red necrotic lesion. However the symptoms on older trees range from the development of large chocolate brown, irregularly shaped, cauliflower-like or whip-like galls on the stem, branch, petiole, shoot, pod, seed or flower stalk. The surfaces of mature galls were generally covered with cinnamon-coloured spores. The older galls become reddish brown which eventually turned black and they are commonly invaded by tunneling insects. Based on the rate of infection, cumulative mortality due to gall rust disease and the effect of gall rust disease on relative growth rate, seedlings from Wamena seed source were moderately resistant that this was the best seed source of the eleven seed sources tested. Generally, the effect of gall rust disease in decreasing the relative growth rate of seedlings was only significantly different at 47 DAI, particularly for seedlings from RO5/95 and Walang Gintang seed sources. Resistance to gall rust disease was accounted by approximately 41-46% of genetic and 54–59% of environmental factors respectively. The qualitative character of height was accounted for by approximately 50-84% and 16-50% of genetic and environmental factors respectively. The genetic correlation between gall rust disease severity and height of seedling was high (85%) and positive, particularly at 27 DAI. The genetic diversity of eleven seed sources F. moluccana seedlings assessed using RAPDs technique was small, with 1.036-1.094 effective alleles, 34-55 polymorphic loci, 35.05% to 56.76% proportion of polymorphic loci, Shannon Diversity Index of 0.115-0.192 and Nei's Diversity Index of 0.18-0.29. In addition, the genetic distance between seed sources was narrow (0.036 to 0.152). All seedlings from Brumas seed sources (RO2, RO5, R2001 and 2S/75) were closely related to those from East Timor, East Flores, Moluccas and Java, but were distant from Wamena. There were negative and small relationship between polymorphic loci, Shannon's Diversity Index, Nei's Diversity Index and gall rust disease severity at 7, 17 and 27 DAI (R2 = 4% to 27%). However, their relationship at 37 and 47 DAI were positive and relatively moderate (R2 = 39% to 49%). Thus, the correlations between genetic variation and gall rust disease severity of F. moluccana seedlings were inconsistent by times and their relationship was not strong. Since gall rust disease resistance was accounted by genetic and environmental factors almost at the same proportion, applying integrated gall rust management control becomes essential. Site selection, using genetically resistant material, regular monitoring, pruning, thinning in the field and chemical control in the nursery are principle methods for preventing gall rust disease of F. moluccana at Brumas Estate.